2006
DOI: 10.1093/brain/awl174
|View full text |Cite
|
Sign up to set email alerts
|

Early onset severe and late-onset mild Charcot-Marie-Tooth disease with mitofusin 2 (MFN2) mutations

Abstract: Mutations in the mitofusin 2 (MFN2) gene, which encodes a mitochondrial GTPase mitofusin protein, have recently been reported to cause both Charcot-Marie-Tooth 2A (CMT2A) and hereditary motor and sensory neuropathy VI (HMSN VI). It is well known that HMSN VI is an axonal CMT neuropathy with optic atrophy. However, the differences between CMT2A and HMSN VI with MFN2 mutations remained to be clarified. Therefore, we studied the phenotypic characteristics of CMT patients with MFN2 mutations. Mutations in MFN2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
263
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(303 citation statements)
references
References 45 publications
33
263
3
4
Order By: Relevance
“…The amino acid residue at position 94 of the Mfn2 protein displays a mutation rate much higher than any other site. Mutations in this codon have been reported 13 times in independent patients suffering from CMT2A (5 times R94W and 7 times R94Q) (Cho et al, 2007;Chung et al, 2006;Kijima et al, 2005;Neusch et al, 2007;Verhoeven et al, 2006;Zuchner et al, 2004). This position is not located in the GTPase domain but immediately upstream of it.…”
Section: Mitofusins and Mitochondrial Fusionmentioning
confidence: 98%
See 3 more Smart Citations
“…The amino acid residue at position 94 of the Mfn2 protein displays a mutation rate much higher than any other site. Mutations in this codon have been reported 13 times in independent patients suffering from CMT2A (5 times R94W and 7 times R94Q) (Cho et al, 2007;Chung et al, 2006;Kijima et al, 2005;Neusch et al, 2007;Verhoeven et al, 2006;Zuchner et al, 2004). This position is not located in the GTPase domain but immediately upstream of it.…”
Section: Mitofusins and Mitochondrial Fusionmentioning
confidence: 98%
“…Typical clinical symptoms of CMT2A are progressive distal limb muscle weakness and/or atrophy, stepping gait, distal sensory loss, and mobility impairment, which can lead to wheelchair dependency. Puzzlingly, the disease onset seems to be very diverse from one case to another but seems to be tightly related to disease severity; the sooner symptoms will appear the more severe they will be (Chung et al, 2006). Accordingly, the number of peripheral axons in the sural nerve Experimental Neurology 218 (2009) [268][269][270][271][272][273] of early onset patients is dramatically reduced while it appears unchanged in late onset patients (Chung et al, 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported that the phenotype is markedly different in early (<10 years) and late disease-onset (>10 years) CMT groups with MFN2 mutations, where patients with early onset usually involve severe cases and most patients with late onset show mild symptoms (Chung et al, 2006;Banchs et al, 2008). The same phenomenon occurred in this family, where 3 patients with severe disease status had early onset (the proband, χ:2 and χ:5) at 8, 6 and 11 years, respectively; they had malformation in extremities and severe muscle atrophy and were even wheelchair-bound.…”
Section: Discussionmentioning
confidence: 99%